Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.30699/jogcr.3.3.123
|View full text |Cite
|
Sign up to set email alerts
|

New Management of Gestational trophoblastic diseases; A Continuum of Moles to Choriocarcinoma: A Review Article

Abstract: Unusual presentation of invasive mole: A case report [2] A review of recent findings for obstetricians about combined oral contraceptive pills [3] Ovarian malignant mixed germ cell tumor: A case of unusual presentation as molar pregnancy [4] Clinical gynecologic oncology [5] OC27. 01: Role of imaging in assessment of gestational trophoblastic neoplasia and transvaginal Doppler ultrasound versus pelvic dynamic contrast enhanced MRI [6] Williams Obstetrics [7] Berek and Novak's gynecology [8] Outcome of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Intestinal metastases from choriocarcinoma are rare, occurring in only approximately 5% of patients with choriocarcinoma; lower gastrointestinal metastases are even rarer, but intestinal metastases often predict a poor prognosis [ 8 , 9 ]. This disease was first described by Sears JB et al in 1933, and only 27 cases have been reported to date in the English literature (partially shown in Table 2 [ 5 , 10 – 19 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal metastases from choriocarcinoma are rare, occurring in only approximately 5% of patients with choriocarcinoma; lower gastrointestinal metastases are even rarer, but intestinal metastases often predict a poor prognosis [ 8 , 9 ]. This disease was first described by Sears JB et al in 1933, and only 27 cases have been reported to date in the English literature (partially shown in Table 2 [ 5 , 10 – 19 ]).…”
Section: Discussionmentioning
confidence: 99%